Lessons for patient experience from the voices of pediatrics and children's hospitals - Jason Wolf (The Beryl Institute, 2018)
This special issue on patient & family experience in children's hospitals and pediatric care underlines pediatrics' position as a leader in the experience journey. In pediatrics and children's hospitals significant efforts are made to the ensure the environment is welcoming and comfortable, there is a commitment to communicating to patients - the children that are cared for - in a way they can understand, and there is a clear intention of engaging family members as an integral part of the care experience. In acknowledging that this is a special issue on pediatrics, we would miss a significant opportunity if we were not to look for and find the lessons that can be applied across healthcare settings. It is this capacity to transcend boundaries in which true experience improvement will be realized.